Perceptions and conditions for sustainable energy and tourism development in Bali’s villages, Indonesia - DK Halim; Dinar Sukma Pramesti; Jatmiko Wahyu Nugroho; Dwi Novita Cahyaningtyas Permatasari (Journal of Rural Tourism, 2026)
Purpose - This study aims to examine community-level conditions and perceptions related to sustainable energy and tourism development in four Balinese villages—Banjarasem, Blimbingsari, Bongan, and Bantas. It seeks to identify how local demographics, economic sectors, and attitudes toward renewable energy influence sustainable rural development.  Methodology/Design/Approach - Using community-level survey data, the study analyzes local perspectives on tourism engagement, renewable energy preferences, energy stability, financial considerations, and the perceived importance of green areas. Descriptive and comparative analyses were conducted to reveal trends and contextual differences among the four villages.  Findings - Results show a strong community interest in adopting renewable energy, particularly Solar PV, though cost and limited technical understanding remain major barriers. Energy instability affects both public facilities and productive sectors such as agriculture and tourism. Despite these challenges, residents express a willingness to pay more for green energy and show interest in accessing credit facilities to support sustainable initiatives. Originality/Value - This study provides empirical insights into the intersection of rural energy transition and tourism development in Bali. By integrating community-level perceptions with sectoral energy needs, it offers valuable input for public administration strategies that aim to design inclusive, context-sensitive policies for sustainable rural transformation.